Analysis of the Influence of Leadership and Compensation Style on Employee Performance with Competence as an Intervening Variable at PT. Pelabuhan Indonesia - Agus May Suryanto; Hermien Tridayanti; Joko Suyono (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: Think about the role that employee competency plays in the relationship between leadership style, salary, and performance. Design/methodology/approach: Quantitative research. Findings: 1) The way a leader acts has a major, favorable impact on the results his or her team achieves, 2) leadership style significantly positively affects competence, 3), pay raises have a positive impact on productivity, 4) Raises in salary have a salutary effect on worker performance., 5) employee competence has a positive impact on productivity, 6).Positive results can be attained through a variety of leadership styles on productivity through an intermediary of employee competence. 7) With competence as a moderating element, salary has a large, positive effect on worker output. Research limitations/implications: This study surveyed the staff of PT. Pelabuhan Indonesia (Persero) utilizing a sample size of 300 people who filled out questionnaires provided in-house. The collected data was analyzed using Smart PLS version 3.2.9. Practical implications: This study shows that both leadership style and pay have significant impacts on workers' output. Competence has a significant impact on performance and outcomes such as salary and leadership style. Competence is an intermediary factor between leadership style and compensation and staff performance. Originality/value: This Paper is Original Paper type: Research paper